Parental Knowledge About Dental Health in Children - Anhusadar, Laode; Islamhiyah, Islamhiyah (KnE Social Sciences, 2022)
Parental knowledge is crucial in the development of behavior that promotes or discourages children’s dental and oral hygiene. The goal of this research was to investigate how much knowledge parents had about their children’s oral health. Interviews and questionnaires were used to gather information. The findings revealed that the majority of parents were unaware of their children’s oral health. On the other hand, parents with sufficient knowledge did not always practice good oral hygiene, and parents with less knowledge did not always raise unhealthy children. While knowledge is one of the determinants of dental and oral hygiene in children, other factors such as parents’ attitudes and awareness have an impact on the role of parents in maintaining their children’s dental health. Keywords: parental knowledge, dental health, early childhood